2022
DOI: 10.1007/s10439-022-02917-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fall Direction and Hip Protector on Fracture Risk: FE Model Predictions Driven by Experimental Data

Abstract: Hip fractures in older adults, which often lead to lasting impairments and an increased risk of mortality, are a major public health concern. Hip fracture risk is multi-factorial, affected by the risk of falling, the load acting on the femur, and the load the femur can withstand. This study investigates the influence of impact direction on hip fracture risk and hip protector efficacy. We simulated falls for 4 subjects, in 7 different impact directions (15° and 30° anterior, lateral, and 15°, 30°, 60°, and 90° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
(110 reference statements)
1
2
0
Order By: Relevance
“…The results from the current study are supported by several previous studies (Choi and Robinovitch, 2018;Feldman and Robinovitch, 2007;van den Kroonenberg et al, 1995;Galliker et al, 2022). The proximal femur Frontiers in Bioengineering and Biotechnology frontiersin.org forces decrease as the trunk angle changes from 10 to 80 °.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results from the current study are supported by several previous studies (Choi and Robinovitch, 2018;Feldman and Robinovitch, 2007;van den Kroonenberg et al, 1995;Galliker et al, 2022). The proximal femur Frontiers in Bioengineering and Biotechnology frontiersin.org forces decrease as the trunk angle changes from 10 to 80 °.…”
Section: Discussionsupporting
confidence: 91%
“…They found that the 10-degree anterior pelvis rotation leads to the highest load on the femoral neck (Choi and Robinovitch, 2018). A recent subject-specific finite element simulation study (Galliker et al, 2022) indicated that the femoral neck reaction forces which was quantified at the acetabulum were higher in lateral or 15 °anterior pelvis rotations compared to other anterior (30 °) or posterior rotations (15, 30, 60, and 90 °).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, the meta-analysis included in this study did not discuss the effect of the angle at the time of fall on hip fracture incidence. A study using biofidelic finite element models showed that the incidence of hip fractures was highest when the direction of impact was lateral, as was 15 degrees posterior [ 44 ]. And this angle was also in the greatest range of the hip protector attenuation in peak compressive stress [ 45 ].…”
Section: Discussionmentioning
confidence: 99%